Prevalence and Determinants of Haemoparasitic Protozoal Infections among Children Attending Selected Public and Private Health Facilities in Numan Metropolis, Adamawa State, Nigeria - Yafiryau, E.P; A.K., Mijah; H.I.J., Agere; U.E., John-Zakka; S.H., Nengean (African Journal of Medicine, Surgery and Public Health Research, 2026)
Haemoparasitic protozoal infections, particularly malaria, pose a substantial public health burden in sub-Saharan Africa, with limited data on facility-specific prevalence in underserved regions such as Numan Metropolis, Nigeria. This study aimed to determine the prevalence of these infections among children attending public and private health facilities and identify key determinants. A cross-sectional study was conducted among 400 children aged 1–15 years recruited via multistage sampling from four facilities (two public, two private) in Numan Metropolis. Thick blood films were stained with 10% Giemsa for 30 minutes and examined microscopically for Plasmodium, Trypanosoma, and Babesia species, with parasite density classified per World Health Organization guidelines. A structured, pre-tested questionnaire assessed demographic, socioeconomic, environmental, and behavioral factors. Data were analyzed using SPSS version 25, with chi-square tests for associations (p < 0.05). Ethical approval was obtained from the Adamawa State Ministry of Health Institutional Review Board. Overall prevalence was 45.0% (180/400), predominantly Plasmodium falciparum (100% of positives; no Trypanosoma or Babesia detected). Prevalence was higher in private facilities (52.0%) than public ones (38.0%; χ² = 7.92, p = 0.005). Light infections predominated (61.67%), with no significant intensity differences across facilities (χ² = 0.45, p = 0.931). Significant associations included stagnant water exposure (χ² = 12.3, p = 0.001) and inconsistent insecticide-treated net (ITN) use (χ² = 9.8, p = 0.002); no significant age or gender differences were observed (χ² = 2.1, p = 0.35 and χ² = 0.4, p = 0.53, respectively). Complications included anemia (45.0% of cases) and school absenteeism (73.0%). Haemoparasitic infections remain highly endemic, exacerbated by environmental and behavioral risks. Targeted interventions, including enhanced ITN distribution and sanitation improvements, are essential to align with Nigeria's National Malaria Strategic Plan and Sustainable Development Goal 3. These findings underscore the need for equitable healthcare access in riverine settings.